Heterotopic ossification of the ulnar collateral ligament: a description of a case in a top level weightlifting athlete - Giombini, A.; Innocenzi, L.; Massazza, G.; Fagnani, F.; Ripani, M.; Pigozzi, F. (The Journal of Sports Medicine and Physical Fitness, 2005)
The purpose of this paper is to describe a case of heterotopic ossification of the ulnar collateral ligament in a 29-year-old top level weightlifter. Plain radiography of the elbow determined the extent and location of heterotopic ossification. Ultrasound and MR imaging completed the instrumental set-up. This symptomatic case had the resolution of pain after 2 months of a supervised rehabilitation program. At one year follow-up the athlete is asymptomatic referring occasional minor pain only in the periods of vigorous training.